Impact of maternal BMI and sampling strategy on the concentration of leptin, insulin, ghrelin and resistin in breast milk across a single feed: a longitudinal cohort study. Issue 7 (7th July 2016) - Andreas, Nicholas J; Hyde, Matthew J; Herbert, Bronwen R; Jeffries, Suzan; Santhakumaran, Shalini; Mandalia, Sundhiya; Holmes, Elaine; Modi, Neena
Abstract : Objectives: We tested the hypothesis that there is a positive association between maternal body mass index (BMI) and the concentration of appetite-regulating hormones leptin, insulin, ghrelin and resistin in breast milk. We also aimed to describe the change in breast milk hormone concentration within each feed, and over time. Setting: Mothers were recruited from the postpartum ward at a university hospital in London. Breast milk samples were collected at the participants' homes. Participants: We recruited 120 healthy, primiparous, breastfeeding mothers, aged over 18 years. Mothers who smoked, had multiple births or had diabetes were excluded. Foremilk and hindmilk samples were collected from 105 women at 1 week postpartum and 92 women at 3 months postpartum. Primary and secondary outcome measures: We recorded maternal and infant anthropometric measurements at each sample collection and measured hormone concentrations using a multiplex assay. Results: The concentration of leptin in foremilk correlated with maternal BMI at the time of sample collection, at 7 days (r=0.31, p=0.02) and 3 months postpartum (r=0.30, p=<0.00). Foremilk insulin correlated with maternal BMI at 3 months postpartum (r=0.22, p=0.04). Breast milk ghrelin and resistin were not correlated with maternal BMI. Ghrelin concentrations at 3 months postpartum were increased in foremilk compared with hindmilk (p=0.01). Concentrations of ghrelin were increased in hindmilk collected at 1  week postpartum compared with samples collected at 3 months postpartum (p=0.03). A trend towards decreased insulin concentrations in hindmilk was noted. Concentrations of leptin and resistin were not seen to alter over a feed. Conclusions: A positive correlation between maternal BMI and foremilk leptin concentration at both time points studied, and foremilk insulin at 3 months postpartum was observed. This may have implications for infant appetite regulation and obesity risk.